2018
DOI: 10.1080/07481187.2017.1411991
|View full text |Cite
|
Sign up to set email alerts
|

Presence of trauma and suicide risk: Personal control as a moderator

Abstract: Given past findings that have linked trauma and lack of personal control to greater suicidal risk in adults, the present study examined how trauma presence and personal control are uniquely involved in predicting suicidal risk in a sample of 469 college students. Regression analyses indicated that both trauma presence and personal control were significant predictors of suicidal risk, as was their interaction. The present findings suggest a need to consider both trauma presence and low personal control in asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly to other countries, China is reporting a high prevalence of suicidal behavior among young people, including college students (7)(8)(9). Transitioning from adolescence to young adults, university students are considered as the future elite; however, academic and career expectations from themselves and their parents, competitive environments, achieving less than hoped, and failing a grade may lead to interpersonal conflicts and a sense of isolation, and further to stress, low personal control, autistic traits, internet addiction, depression, anxiety, and suicidal thoughts and attempts (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to other countries, China is reporting a high prevalence of suicidal behavior among young people, including college students (7)(8)(9). Transitioning from adolescence to young adults, university students are considered as the future elite; however, academic and career expectations from themselves and their parents, competitive environments, achieving less than hoped, and failing a grade may lead to interpersonal conflicts and a sense of isolation, and further to stress, low personal control, autistic traits, internet addiction, depression, anxiety, and suicidal thoughts and attempts (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Self-control as a mediator variable Some researchers have identified a moderating effect of low self-control on the risky behaviors of adolescents. For example, Chang et al (2018) showed that self-control moderates the relationship between trauma and suicidal behaviors, and Rising and Bol (2017) presented the moderating influence of self-control in the relationship between labels that specify the number of calories and food choice. Liu, Oshri, and Duprey (2020) identified self-control as the moderator of the relationship between childhood maltreatment and alcohol-related problems, while Lindgren, Neighbors, Westgate, and Salemink (2014) have observed that self-control moderates the link between drinking identity and alcohol consumption, respectively alcohol issues.…”
Section: Figurementioning
confidence: 99%
“…Well-being outcomes: PYD, social emotional competencies, and mental health Reducing depression and suicidal ideation in the wake of adversity and trauma involves decreasing anxiety and increasing the inhibitory mediating factors of (a) self-regulation, (b) recognition of personal strengths, and (c) better social relationships (Briere & Scott, 2015, pp. 165-213;Chang et al, 2018;Sheline & Ros en, 2017) -all hallmarks of PYD and social and emotional learning (SEL) competencies.…”
Section: Hip Hop: Communities Equity and Justicementioning
confidence: 99%
“…It involves using the process of creating, analyzing, and reconstructing artistic pieces as an empowering process (Travis, 2016, p. 199). It recognizes that opportunities for positive development after trauma and adversity, such as (a) self-control (Chang et al, 2018) and (b) post-traumatic growth factors -like better relating to others, acknowledging personal strengths, and recognizing new possibilities (Sheline & Ros en, 2017) -can promote resilience (Werner & Johnson, 2004). Prior research has demonstrated efficacy in using elements of the HHE model (Travis, Rodwin, et al, 2019).…”
Section: Hip Hop and Empowermentmentioning
confidence: 99%